Associations Between Macronutrients From Different Dietary Sources and Serum Lipids in 24 639 UK Biobank Study Participants. Issue 7 (27th May 2021) - Kelly, Rebecca K.; Watling, Cody Z.; Tong, Tammy Y.N.; Piernas, Carmen; Carter, Jennifer L.; Papier, Keren; Key, Timothy J.; Perez-Cornago, Aurora
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Macronutrients may relate differently with serum lipids depending on their source, and understanding this relationship is important for cardiovascular disease prevention. We aimed to investigate the associations between macronutrients and macronutrients from different sources with serum lipids in UK Biobank. Approach and Results: Serum lipids were obtained from serum collected at baseline in 24 639 participants with diet assessed using ≥2 twenty-four–hour dietary assessments completed at baseline and during follow-up. Multivariable linear regressions were conducted to calculate geometric mean concentrations of serum lipids by quintiles of macronutrients. We modeled the association between isoenergetic substitution of 5% energy intake from saturated fatty acids (SFA) with other macronutrients and serum lipids. Free sugar intake was positively associated with triglycerides (0.15 mmol/L geometric mean difference between highest and lowest quintile of intake [95% CI, 0.12–0.17 mmol/L]), whereas nonfree sugar intake was inversely associated with triglycerides (−0.08 [−0.10 to −0.05]). SFA intake was positively associated with LDL-C (low-density lipoprotein cholesterol; 0.17 [0.13–0.20]), omega-3 fatty acid intake was inversely associated with triglycerides (−0.15 [−0.17 to −0.12]). Modeled substitution of SFA with polyunsaturated fatty acids was associated with lower total cholesterol, LDL-C, and triglycerides. Conclusions: The relationship between carbohydrates and triglycerides may depend on their quality, and reducing free sugar intake may be important in cardiovascular disease prevention. Consistent with previous studies, SFA intake is associated with LDL-C and substitution of SFA intake with polyunsaturated fatty acids intake may be associated with a more favorable serum lipid profile.